2007
DOI: 10.1158/0008-5472.can-06-3462
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Tomato and Broccoli Enhance Antitumor Activity in Dunning R3327-H Prostate Adenocarcinomas

Abstract: The consumption of diets containing 5 to 10 servings of fruits and vegetables daily is the foundation of public health recommendations for cancer prevention, yet this concept has not been tested in experimental models of prostate cancer. We evaluated combinations of tomato and broccoli in the Dunning R3327-H prostate adenocarcinoma model. Male Copenhagen rats (n = 206) were fed diets containing 10% tomato, 10% broccoli, 5% tomato plus 5% broccoli (5:5 combination), 10% tomato plus 10% broccoli (10:10 combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 45 publications
9
129
1
Order By: Relevance
“…In rats, tomato supplementation reduces carcinogenesis-induced mortality more efficiently than lycopene (13)(14)(15). Again, in the Dunning R3327-H prostate cancer model, the intake of whole foods, such as tomatoes and broccoli, slowed tumor growth more effectively than lycopene alone (16). Tomatoes contain other anticancer phytochemicals [see U.S. Department of Agriculture National Nutrient Database for Standard Reference: release 19 (2006), pdf available from http://www.nal.usda.gov/fnic/ foodcomp/cgi-bin/measure.pl?MSRE_NO=11548xyz1100 xyzTomato%20powderxyzxyz], whereas constituents already present in small amounts or newly formed during processing also contribute to their final in vivo efficacy (14).…”
Section: Introductionmentioning
confidence: 98%
“…In rats, tomato supplementation reduces carcinogenesis-induced mortality more efficiently than lycopene (13)(14)(15). Again, in the Dunning R3327-H prostate cancer model, the intake of whole foods, such as tomatoes and broccoli, slowed tumor growth more effectively than lycopene alone (16). Tomatoes contain other anticancer phytochemicals [see U.S. Department of Agriculture National Nutrient Database for Standard Reference: release 19 (2006), pdf available from http://www.nal.usda.gov/fnic/ foodcomp/cgi-bin/measure.pl?MSRE_NO=11548xyz1100 xyzTomato%20powderxyzxyz], whereas constituents already present in small amounts or newly formed during processing also contribute to their final in vivo efficacy (14).…”
Section: Introductionmentioning
confidence: 98%
“…Our laboratory has demonstrated in an N-methyl-N-nitrosurea (MNU)-androgen induced rat carcinogenesis model and in a Dunning R-3327H transplantable prostate adenocarcinoma model, that diets containing 10% whole tomato powder significantly inhibited the development of prostate cancer as compared to a control diet, whereas a LYC-supplemented diet was not as effective [11,12]. Short-term clinical studies with prostate cancer patients have reported therapeutic benefits with tomato supplementation, including reductions in prostate size, leukocyte DNA damage, and prostate specific antigen levels, as well as positively modulated volume and grade of prostate intraepithelial neoplasia, and also altered biomarkers of prostate cell growth and differentiation [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Using the same animal model it was found that fed male Copenhagen rats with diets containing 10% broccoli, decreased tumor weight by 42%. Tumor growth reduction was associated with reduced proliferation and increased apoptosis [87]. Moreover, treatment of mice with DIM inhibits tumor formation of TRAMP cells, mouse prostate cancer cells [88].…”
Section: Med Chemmentioning
confidence: 97%